a crazy equation

Algebra Level 4

what is the value of (∛8+(√21))+(∛8-(√21))?

assume the answer is real and it is a 1 digit number (0 is not counted!)


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

The answer should be 8 3 + 21 + 8 3 21 = 2 + 2 = 4 \sqrt[3]{8}+ \sqrt{21}+ \sqrt[3]{8}-\sqrt{21} =2+2=\boxed{4}

The problem is incorrect in my opinion. This needs correct LaTex formatting to be clear and the question should be 8 + 3 21 3 + 8 3 21 3 \sqrt[3]{{8}+3\sqrt{21}}+\sqrt[3]{{8}-3\sqrt{21}} to give answer 1 \boxed{1} .

L Chua
May 16, 2020

Let’s write:

a = 8 + 3√21 b = 8 – 3√21

So then:

x = ∛a + ∛b

Notice that the cube roots of a and b are real numbers (since every real number has a real cube root), so the value of x we want is also a real number. To simplify, let’s cube both sides:

x3 = (∛a + ∛b)3

x3 = a + b + 3(∛a)2(∛b) + 3(∛b)2(∛a)

We can then write two copies of each squared term, and then group the cube roots, to get:

x3 = a + b + 3∛(a(ab)) + 3∛(b(ba))

Now we utilize that a and b are square root conjugates, so we can simplify to a whole number:

ab = ba = (8 + 3√21)(8 – 3√21) = 64 – 9(21) = -125 = (-5)3

Substituting back and simplifying gives:

x3 = a + b + 3∛(a(-5)3) + 3∛(b(-5)3)

x3 = a + b + 3(-5)(∛a) + 3(-5)(∛b)

x3 = a + b – 15(∛a + ∛b)

Now recall x = ∛a + ∛b, which means:

x3 = a + b – 15x

Furthermore a + b = 16, so we get a simple polynomial:

x3 = 16 – 15x x3 + 15x – 16 = 0

We want to find a real value of x. One strategy is to use special values, and we get lucky in this case: x = 1 is a solution.

Consequently, (x – 1) is a factor. We can factor to check for other solutions, and we get:

(x – 1)(x2 + x + 16) = 0, but 0 is not counted (check the problem!)

The quadratic equation can be solved using the quadratic formula, but both of its roots will have non-zero imaginary parts. These are extraneous roots since the original expression was a real number.

Hence, we have the solution:

1 = ∛(8 + 3√21) + ∛(8 – 3√21)

The problem is incorrect in my opinion. This needs correct LaTex formatting to be clear and the question should be 8 + 3 21 3 + 8 3 21 3 \sqrt[3]{{8}+3\sqrt{21}}+\sqrt[3]{{8}-3\sqrt{21}} to give answer 1 1 .

Vinayak Srivastava - 1 year ago

6 pending reports

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...